Measuring quality of life in Chinese cancer patients: A new version of the Functional Living Index for Cancer (Chinese) - Cheung, YB (ACAD MEDICINE SINGAPORE, 2023)
ANNALS ACADEMY OF MEDICINE SINGAPORE